Comparative study on distributed generation trading mechanisms in the UK and China. Issue 3 (22nd June 2022) - Yao, Yunting; Gao, Ciwei; Li, Shiyao; Zhou, Yue; Wang, Dan; Song, Meng
Abstract: The market penetration of distributed generation (DG), particularly for that from renewables, has significantly increased in recent years. This trend will continue with the low‐carbon transition of electric power systems, as a part of global efforts to combat climate change. Appropriate trading mechanisms are of great importance for incentivizing the investment in and coordinated operation of DG. The UK and China both have ambitious decarbonization agendas with particular emphasis on the electricity market design. Nevertheless, the UK and China have distinguishing features in electricity market design, particularly in the trading mechanisms for DG. This paper presents a thorough review of DG trading policies and arrangements in both countries, including market structures, connection classifications, economic benefits and practical issues. The strengths, weaknesses, opportunity, and threats‐political, economical, social and technological (SWOT‐PEST) model features of the mechanisms in both countries were qualitatively identified and compared. A quantitative comparison was conducted between the trading arrangements in the UK and China, with the economic benefits analysed and the implications revealed. Finally, the directions for developing and improving DG trading mechanisms were suggested based on the comparative analysis. The practical experiences of the UK and China can be extended to other countries across the globe.